Chemical Partitioning and Speciation of Some Trace Elements in Soil and Street Dust - Yousif Ahmed, Amel; A.H. Eltayeb, Mohammed; Khalik Wood, Abdul; Suhaimi Hamza, Moh.; Pauzi Abdulah, Md. (Asian Journal of Chemistry, 2011)
Chemical fraction technique and atomic absorption spectrometry (AAS) were used to determine the presence of Cr, Mn, Fe, Cu, Zn, Pb in surface soil samples and street dust collected from areas exposed to industrial and traffic emission and agricultural areas in Khartoum state, Sudan. Principle component analysis was carried out as an statistical method.